{-# OPTIONS --allow-unsolved-metas #-} module Putil where open import Level hiding ( suc ; zero ) open import Algebra open import Algebra.Structures open import Data.Fin hiding ( _<_ ; _≤_ ; _-_ ; _+_ ; _≟_) open import Data.Fin.Properties hiding ( <-trans ; ≤-trans ; ≤-irrelevant ; _≟_ ) renaming ( <-cmp to <-fcmp ) open import Data.Fin.Permutation open import Function hiding (id ; flip) open import Function.Inverse as Inverse using (_↔_; Inverse; _InverseOf_) open import Function.LeftInverse using ( _LeftInverseOf_ ) open import Function.Equality using (Π) open import Data.Nat -- using (ℕ; suc; zero; s≤s ; z≤n ) open import Data.Nat.Properties -- using (<-trans) open import Relation.Binary.PropositionalEquality open import Data.List using (List; []; _∷_ ; length ; _++_ ; head ; tail ) renaming (reverse to rev ) open import nat open import Symmetric open import Relation.Nullary open import Data.Empty open import Relation.Binary.Core open import Relation.Binary.Definitions open import fin -- An inductive construction of permutation pprep : {n : ℕ } → Permutation n n → Permutation (suc n) (suc n) pprep {n} perm = permutation p→ p← record { left-inverse-of = piso→ ; right-inverse-of = piso← } where p→ : Fin (suc n) → Fin (suc n) p→ zero = zero p→ (suc x) = suc ( perm ⟨$⟩ʳ x) p← : Fin (suc n) → Fin (suc n) p← zero = zero p← (suc x) = suc ( perm ⟨$⟩ˡ x) piso← : (x : Fin (suc n)) → p→ ( p← x ) ≡ x piso← zero = refl piso← (suc x) = cong (λ k → suc k ) (inverseʳ perm) piso→ : (x : Fin (suc n)) → p← ( p→ x ) ≡ x piso→ zero = refl piso→ (suc x) = cong (λ k → suc k ) (inverseˡ perm) pswap : {n : ℕ } → Permutation n n → Permutation (suc (suc n)) (suc (suc n )) pswap {n} perm = permutation p→ p← record { left-inverse-of = piso→ ; right-inverse-of = piso← } where p→ : Fin (suc (suc n)) → Fin (suc (suc n)) p→ zero = suc zero p→ (suc zero) = zero p→ (suc (suc x)) = suc ( suc ( perm ⟨$⟩ʳ x) ) p← : Fin (suc (suc n)) → Fin (suc (suc n)) p← zero = suc zero p← (suc zero) = zero p← (suc (suc x)) = suc ( suc ( perm ⟨$⟩ˡ x) ) piso← : (x : Fin (suc (suc n)) ) → p→ ( p← x ) ≡ x piso← zero = refl piso← (suc zero) = refl piso← (suc (suc x)) = cong (λ k → suc (suc k) ) (inverseʳ perm) piso→ : (x : Fin (suc (suc n)) ) → p← ( p→ x ) ≡ x piso→ zero = refl piso→ (suc zero) = refl piso→ (suc (suc x)) = cong (λ k → suc (suc k) ) (inverseˡ perm) psawpn : {n : ℕ} → 1 < n → Permutation n n psawpn {suc zero} (s≤s ()) psawpn {suc n} (s≤s (s≤s x)) = pswap pid pfill : { n m : ℕ } → m ≤ n → Permutation m m → Permutation n n pfill {n} {m} m≤n perm = pfill1 (n - m) (n-m ¬a ¬b c = x p← : Fin (suc (suc n)) → Fin (suc (suc n)) p← zero = fromℕ< (s≤s (s≤s m≤n)) p← (suc x) with <-cmp (toℕ x) (suc m) ... | tri< a ¬b ¬c = fromℕ< (≤-trans (fin ¬a ¬b c = suc x mm : toℕ (fromℕ< {suc m} {suc (suc n)} (s≤s (s≤s m≤n))) ≡ suc m mm = toℕ-fromℕ< (s≤s (s≤s m≤n)) mma : (x : Fin (suc n) ) → suc (toℕ x) ≤ suc m → toℕ ( fromℕ< (≤-trans (fin ¬a ¬b c = p16 (suc x) refl where p16 : (y : Fin (suc (suc n))) → y ≡ suc x → p← y ≡ suc x p16 zero eq = ⊥-elim ( nat-≡< (cong (λ k → suc (toℕ k) ) eq) (s≤s (s≤s (z≤n)))) p16 (suc y) eq with <-cmp (toℕ y) (suc m) -- suc (suc m) < toℕ (suc x) ... | tri< a ¬b ¬c = ⊥-elim ( nat-≡< refl ( ≤-trans c (subst (λ k → k < suc m) p17 a )) ) where -- x = suc m case, c : suc (suc m) ≤ suc (toℕ x), a : suc (toℕ y) ≤ suc m, suc y ≡ suc x p17 : toℕ y ≡ toℕ x p17 with <-cmp (toℕ y) (toℕ x) | cong toℕ eq ... | tri< a ¬b ¬c | seq = ⊥-elim ( nat-≡< seq (s≤s a) ) ... | tri≈ ¬a b ¬c | seq = b ... | tri> ¬a ¬b c | seq = ⊥-elim ( nat-≡< (sym seq) (s≤s c)) ... | tri≈ ¬a b ¬c = eq ... | tri> ¬a ¬b c₁ = eq ... | tri< a ¬b ¬c = p10 (fromℕ< (≤-trans (s≤s a) (s≤s (s≤s m≤n) ))) refl where p10 : (y : Fin (suc (suc n)) ) → y ≡ fromℕ< (≤-trans (s≤s a) (s≤s (s≤s m≤n) )) → p← y ≡ suc x p10 zero () p10 (suc y) eq = p15 where p12 : toℕ y ≡ suc (toℕ x) p12 = begin toℕ y ≡⟨ cong (λ k → Data.Nat.pred (toℕ k)) eq ⟩ toℕ (fromℕ< (≤-trans a (s≤s m≤n))) ≡⟨ toℕ-fromℕ< {suc (toℕ x)} {suc n} (≤-trans a (s≤s m≤n)) ⟩ suc (toℕ x) ∎ p15 : p← (suc y) ≡ suc x p15 with <-cmp (toℕ y) (suc m) -- eq : suc y ≡ suc (suc (fromℕ< (≤-pred (≤-trans a (s≤s m≤n))))) , a : suc x < suc m ... | tri< a₁ ¬b ¬c = p11 where p11 : fromℕ< (≤-trans (fin y = suc x → toℕ y < suc m ... | tri> ¬a ¬b c = ⊥-elim ( nat-<> c (subst (λ k → k < suc m) (sym p12) a )) piso← : (x : Fin (suc (suc n)) ) → p→ ( p← x ) ≡ x piso← zero with <-cmp (toℕ (fromℕ< (s≤s (s≤s m≤n)))) (suc m) | mm ... | tri< a ¬b ¬c | t = ⊥-elim ( ¬b t ) ... | tri≈ ¬a b ¬c | t = refl ... | tri> ¬a ¬b c | t = ⊥-elim ( ¬b t ) piso← (suc x) with <-cmp (toℕ x) (suc m) ... | tri> ¬a ¬b c with <-cmp (toℕ (suc x)) (suc m) ... | tri< a ¬b₁ ¬c = ⊥-elim ( nat-<> a (<-trans c a ¬a₁ ¬b₁ c₁ = refl piso← (suc x) | tri≈ ¬a b ¬c with <-cmp (toℕ (suc x)) (suc m) ... | tri< a ¬b ¬c₁ = ⊥-elim ( nat-≡< b (<-trans a ¬a₁ ¬b c = refl piso← (suc x) | tri< a ¬b ¬c with <-cmp (toℕ ( fromℕ< (≤-trans (fin ¬a ¬b₁ c = ⊥-elim ( ¬a (s≤s (mma x a))) ... | tri< a₁ ¬b₁ ¬c₁ = p0 where p2 : suc (suc (toℕ x)) ≤ suc (suc n) p2 = s≤s (fin ¬a ¬b c = ⊥-elim (nat-≤> c q ¬a ¬b c = ⊥-elim (nat-≤> c q : {n : ℕ } {x : FL n } {y : FL n} → x f< y → y f< x → ⊥ f<> (f x x₁ f<> (f (f (f lt lt2 f-≡< : {n : ℕ } {x : FL n } {y : FL n} → x ≡ y → y f< x → ⊥ f-≡< refl (f lt (f ¬a ¬b c = tri> (λ lt → f<> lt (f lt (f ¬a₁ ¬b c = tri> (λ lt → f<> lt (f ¬a ¬b c = no ( ¬a ) shlem→ : {n : ℕ} → (perm : Permutation (suc n) (suc n) ) → (p0=0 : perm ⟨$⟩ˡ (# 0) ≡ # 0 ) → (x : Fin (suc n) ) → perm ⟨$⟩ˡ x ≡ zero → x ≡ zero shlem→ perm p0=0 x px=0 = begin x ≡⟨ sym ( inverseʳ perm ) ⟩ perm ⟨$⟩ʳ ( perm ⟨$⟩ˡ x) ≡⟨ cong (λ k → perm ⟨$⟩ʳ k ) px=0 ⟩ perm ⟨$⟩ʳ zero ≡⟨ cong (λ k → perm ⟨$⟩ʳ k ) (sym p0=0) ⟩ perm ⟨$⟩ʳ ( perm ⟨$⟩ˡ zero) ≡⟨ inverseʳ perm ⟩ zero ∎ shlem← : {n : ℕ} → (perm : Permutation (suc n) (suc n) ) → (p0=0 : perm ⟨$⟩ˡ (# 0) ≡ # 0 ) → (x : Fin (suc n)) → perm ⟨$⟩ʳ x ≡ zero → x ≡ zero shlem← perm p0=0 x px=0 = begin x ≡⟨ sym (inverseˡ perm ) ⟩ perm ⟨$⟩ˡ ( perm ⟨$⟩ʳ x ) ≡⟨ cong (λ k → perm ⟨$⟩ˡ k ) px=0 ⟩ perm ⟨$⟩ˡ zero ≡⟨ p0=0 ⟩ zero ∎ sh2 : {n : ℕ} → (perm : Permutation (suc n) (suc n) ) → (p0=0 : perm ⟨$⟩ˡ (# 0) ≡ # 0 ) → {x : Fin n} → ¬ perm ⟨$⟩ˡ (suc x) ≡ zero sh2 perm p0=0 {x} eq with shlem→ perm p0=0 (suc x) eq sh2 perm p0=0 {x} eq | () sh1 : {n : ℕ} → (perm : Permutation (suc n) (suc n) ) → (p0=0 : perm ⟨$⟩ˡ (# 0) ≡ # 0 ) → {x : Fin n} → ¬ perm ⟨$⟩ʳ (suc x) ≡ zero sh1 perm p0=0 {x} eq with shlem← perm p0=0 (suc x) eq sh1 perm p0=0 {x} eq | () -- 0 ∷ 1 ∷ 2 ∷ 3 ∷ [] → 0 ∷ 1 ∷ 2 ∷ [] shrink : {n : ℕ} → (perm : Permutation (suc n) (suc n) ) → perm ⟨$⟩ˡ (# 0) ≡ # 0 → Permutation n n shrink {n} perm p0=0 = permutation p→ p← record { left-inverse-of = piso→ ; right-inverse-of = piso← } where p→ : Fin n → Fin n p→ x with perm ⟨$⟩ʳ (suc x) | inspect (_⟨$⟩ʳ_ perm ) (suc x) p→ x | zero | record { eq = e } = ⊥-elim ( sh1 perm p0=0 {x} e ) p→ x | suc t | _ = t p← : Fin n → Fin n p← x with perm ⟨$⟩ˡ (suc x) | inspect (_⟨$⟩ˡ_ perm ) (suc x) p← x | zero | record { eq = e } = ⊥-elim ( sh2 perm p0=0 {x} e ) p← x | suc t | _ = t piso← : (x : Fin n ) → p→ ( p← x ) ≡ x piso← x with perm ⟨$⟩ˡ (suc x) | inspect (_⟨$⟩ˡ_ perm ) (suc x) piso← x | zero | record { eq = e } = ⊥-elim ( sh2 perm p0=0 {x} e ) piso← x | suc t | _ with perm ⟨$⟩ʳ (suc t) | inspect (_⟨$⟩ʳ_ perm ) (suc t) piso← x | suc t | _ | zero | record { eq = e } = ⊥-elim ( sh1 perm p0=0 e ) piso← x | suc t | record { eq = e0 } | suc t1 | record { eq = e1 } = begin t1 ≡⟨ plem0 plem1 ⟩ x ∎ where open ≡-Reasoning plem0 : suc t1 ≡ suc x → t1 ≡ x plem0 refl = refl plem1 : suc t1 ≡ suc x plem1 = begin suc t1 ≡⟨ sym e1 ⟩ Inverse.to perm Π.⟨$⟩ suc t ≡⟨ cong (λ k → Inverse.to perm Π.⟨$⟩ k ) (sym e0) ⟩ Inverse.to perm Π.⟨$⟩ ( Inverse.from perm Π.⟨$⟩ suc x ) ≡⟨ inverseʳ perm ⟩ suc x ∎ piso→ : (x : Fin n ) → p← ( p→ x ) ≡ x piso→ x with perm ⟨$⟩ʳ (suc x) | inspect (_⟨$⟩ʳ_ perm ) (suc x) piso→ x | zero | record { eq = e } = ⊥-elim ( sh1 perm p0=0 {x} e ) piso→ x | suc t | _ with perm ⟨$⟩ˡ (suc t) | inspect (_⟨$⟩ˡ_ perm ) (suc t) piso→ x | suc t | _ | zero | record { eq = e } = ⊥-elim ( sh2 perm p0=0 e ) piso→ x | suc t | record { eq = e0 } | suc t1 | record { eq = e1 } = begin t1 ≡⟨ plem2 plem3 ⟩ x ∎ where plem2 : suc t1 ≡ suc x → t1 ≡ x plem2 refl = refl plem3 : suc t1 ≡ suc x plem3 = begin suc t1 ≡⟨ sym e1 ⟩ Inverse.from perm Π.⟨$⟩ suc t ≡⟨ cong (λ k → Inverse.from perm Π.⟨$⟩ k ) (sym e0 ) ⟩ Inverse.from perm Π.⟨$⟩ ( Inverse.to perm Π.⟨$⟩ suc x ) ≡⟨ inverseˡ perm ⟩ suc x ∎ shrink-iso : { n : ℕ } → {perm : Permutation n n} → shrink (pprep perm) refl =p= perm shrink-iso {n} {perm} = record { peq = λ q → refl } shrink-iso2 : { n : ℕ } → {perm : Permutation (suc n) (suc n)} → (p=0 : perm ⟨$⟩ˡ (# 0) ≡ # 0) → pprep (shrink perm p=0) =p= perm shrink-iso2 {n} {perm} p=0 = record { peq = s001 } where s001 : (q : Fin (suc n)) → (pprep (shrink perm p=0) ⟨$⟩ʳ q) ≡ perm ⟨$⟩ʳ q s001 zero = begin zero ≡⟨ sym ( inverseʳ perm ) ⟩ perm ⟨$⟩ʳ ( perm ⟨$⟩ˡ zero ) ≡⟨ cong (λ k → perm ⟨$⟩ʳ k ) p=0 ⟩ perm ⟨$⟩ʳ zero ∎ s001 (suc q) with perm ⟨$⟩ʳ (suc q) | inspect (_⟨$⟩ʳ_ perm ) (suc q) ... | zero | record {eq = e} = ⊥-elim (sh1 perm p=0 {q} e) ... | suc t | e = refl shrink-cong : { n : ℕ } → {x y : Permutation (suc n) (suc n)} → x =p= y → (x=0 : x ⟨$⟩ˡ (# 0) ≡ # 0 ) → (y=0 : y ⟨$⟩ˡ (# 0) ≡ # 0 ) → shrink x x=0 =p= shrink y y=0 shrink-cong {n} {x} {y} x=y x=0 y=0 = record { peq = p002 } where p002 : (q : Fin n) → (shrink x x=0 ⟨$⟩ʳ q) ≡ (shrink y y=0 ⟨$⟩ʳ q) p002 q with x ⟨$⟩ʳ (suc q) | inspect (_⟨$⟩ʳ_ x ) (suc q) | y ⟨$⟩ʳ (suc q) | inspect (_⟨$⟩ʳ_ y ) (suc q) p002 q | zero | record { eq = ex } | zero | ey = ⊥-elim ( sh1 x x=0 ex ) p002 q | zero | record { eq = ex } | suc py | ey = ⊥-elim ( sh1 x x=0 ex ) p002 q | suc px | ex | zero | record { eq = ey } = ⊥-elim ( sh1 y y=0 ey ) p002 q | suc px | record { eq = ex } | suc py | record { eq = ey } = p003 ( begin suc px ≡⟨ sym ex ⟩ x ⟨$⟩ʳ (suc q) ≡⟨ peq x=y (suc q) ⟩ y ⟨$⟩ʳ (suc q) ≡⟨ ey ⟩ suc py ∎ ) where p003 : suc px ≡ suc py → px ≡ py p003 refl = refl FL→perm : {n : ℕ } → FL n → Permutation n n FL→perm f0 = pid FL→perm (x :: fl) = pprep (FL→perm fl) ∘ₚ pins ( toℕ≤pred[n] x ) t40 = (# 2) :: ( (# 1) :: (( # 0 ) :: f0 )) t4 = FL→perm ((# 2) :: t40 ) -- t1 = plist (shrink (pid {3} ∘ₚ (pins (n≤ 1))) refl) t2 = plist ((pid {5} ) ∘ₚ transpose (# 2) (# 4)) ∷ plist (pid {5} ∘ₚ reverse ) ∷ [] t3 = plist (FL→perm t40) -- ∷ plist (pprep (FL→perm t40)) -- ∷ plist ( pprep (FL→perm t40) ∘ₚ pins ( n≤ 0 {3} )) -- ∷ plist ( pprep (FL→perm t40 )∘ₚ pins ( n≤ 1 {2} )) -- ∷ plist ( pprep (FL→perm t40 )∘ₚ pins ( n≤ 2 {1} )) -- ∷ plist ( pprep (FL→perm t40 )∘ₚ pins ( n≤ 3 {0} )) ∷ plist ( FL→perm ((# 0) :: t40)) -- (0 ∷ 1 ∷ 2 ∷ []) ∷ ∷ plist ( FL→perm ((# 1) :: t40)) -- (0 ∷ 2 ∷ 1 ∷ []) ∷ ∷ plist ( FL→perm ((# 2) :: t40)) -- (1 ∷ 0 ∷ 2 ∷ []) ∷ ∷ plist ( FL→perm ((# 3) :: t40)) -- (2 ∷ 0 ∷ 1 ∷ []) ∷ -- ∷ plist ( FL→perm ((# 3) :: ((# 2) :: ( (# 0) :: (( # 0 ) :: f0 )) ))) -- (1 ∷ 2 ∷ 0 ∷ []) ∷ -- ∷ plist ( FL→perm ((# 3) :: ((# 2) :: ( (# 1) :: (( # 0 ) :: f0 )) ))) -- (2 ∷ 1 ∷ 0 ∷ []) ∷ -- ∷ plist ( (flip (FL→perm ((# 3) :: ((# 1) :: ( (# 0) :: (( # 0 ) :: f0 )) ))))) -- ∷ plist ( (flip (FL→perm ((# 3) :: ((# 1) :: ( (# 0) :: (( # 0 ) :: f0 )) ))) ∘ₚ (FL→perm ((# 3) :: (((# 1) :: ( (# 0) :: (( # 0 ) :: f0 )) )))) )) ∷ [] perm→FL : {n : ℕ } → Permutation n n → FL n perm→FL {zero} perm = f0 perm→FL {suc n} perm = (perm ⟨$⟩ʳ (# 0)) :: perm→FL (shrink (perm ∘ₚ flip (pins (toℕ≤pred[n] (perm ⟨$⟩ʳ (# 0))))) (p=0 perm) ) -- perm→FL {suc n} perm = (perm ⟨$⟩ʳ (# 0)) :: perm→FL (remove (# 0) perm) _p<_ : {n : ℕ } ( x y : Permutation n n ) → Set x p< y = perm→FL x f< perm→FL y pcong-pF : {n : ℕ } → {x y : Permutation n n} → x =p= y → perm→FL x ≡ perm→FL y pcong-pF {zero} eq = refl pcong-pF {suc n} {x} {y} eq = cong₂ (λ j k → j :: k ) ( peq eq (# 0)) (pcong-pF (shrink-cong (presp eq p001 ) (p=0 x) (p=0 y))) where p002 : x ⟨$⟩ʳ (# 0) ≡ y ⟨$⟩ʳ (# 0) p002 = peq eq (# 0) p001 : flip (pins (toℕ≤pred[n] (x ⟨$⟩ʳ (# 0)))) =p= flip (pins (toℕ≤pred[n] (y ⟨$⟩ʳ (# 0)))) p001 = subst ( λ k → flip (pins (toℕ≤pred[n] (x ⟨$⟩ʳ (# 0)))) =p= flip (pins (toℕ≤pred[n] k ))) p002 prefl -- t5 = plist t4 ∷ plist ( t4 ∘ₚ flip (pins ( n≤ 3 ) )) t5 = plist (t4) ∷ plist (flip t4) ∷ ( toℕ (t4 ⟨$⟩ˡ fromℕ< a